Rancang bangun pembuatan mesin cetak pelet pakan ternak - Ahmad Rehan Ardiansyah; Edi Widodo; Mulyadi (BKS-TM Indonesia, 2026)
A livestock feed pellet machine is a device designed to improve the efficiency of animal feed production processes. Manual feed production generally requires a longer processing time and often produces pellets with non-uniform sizes. This study aims to design and develop a livestock feed pellet machine with a production capacity of 20 kg/h, focusing on the structural design of the machine frame and screw extruder as the primary components in the pellet-forming process. The research methodology includes field observation, literature review, and a design process based on the VDI 2222 design method. The design process was carried out using SolidWorks software, involving the selection of main components such as an AC electric motor, a pulley and V-belt transmission system, a hopper, a machine frame, and a screw extruder. Structural strength analysis was conducted using the Finite Element Analysis (FEA) method through SolidWorks Simulation under a static load of 150 kg to evaluate the distribution of stress, strain, displacement, and safety factor. The simulation results show that the maximum stress on the machine frame is 72.6 MPa, with a maximum displacement of 9.516 mm and a minimum safety factor of 1.689, indicating that the stress value is still below the material yield strength and the frame structure is considered safe. Meanwhile, the screw extruder component experiences a maximum stress of 6.14 × 10⁴ N/m², a maximum displacement of 8.313 × 10⁻⁶ mm, and a maximum strain of 1.804 × 10⁻⁷, indicating that the resulting deformation is very small and remains within the elastic limit of the material. Based on the design and structural analysis results, the developed livestock feed pellet machine has a safe and stable structural design and is capable of improving the efficiency of feed production. This machine is expected to serve as an alternative solution for farmers to independently produce livestock feed at a more economical cost.